2017
DOI: 10.1161/hypertensionaha.117.09539
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Multiple Arterial Bed Lesions in Patients With Fibromuscular Dysplasia

Abstract: Fibromuscular dysplasia (FMD) commonly affects the renal and cervical arteries but has been described to affect other vascular beds as well. The prevalence of and clinical characteristics associated with multisite FMD (string-of-beds or focal stenoses affecting at least 2 vascular beds) are not known. In the prospective ARCADIA registry (Assessment of Renal and Cervical Artery Dysplasia), symptomatic patients with renal artery (RA) FMD underwent tomographic- or magnetic resonance-angiography from the aortic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
128
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(168 citation statements)
references
References 23 publications
(9 reference statements)
14
128
2
5
Order By: Relevance
“…Despite high rates of aneurysm and/or dissection in patients with FMD [5,9,25,26], neurovascular events occurring after FMD diagnosis were rare (2%) and most often due to spontaneous carotid artery dissection in patients with a history of previous arterial dissection (2 of 3 patients). This suggests that patients with FMD experience a similar rate of new CeAD (1% per year) as compared to patients with spontaneous CeAD in the absence of confirmed FMD [13,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite high rates of aneurysm and/or dissection in patients with FMD [5,9,25,26], neurovascular events occurring after FMD diagnosis were rare (2%) and most often due to spontaneous carotid artery dissection in patients with a history of previous arterial dissection (2 of 3 patients). This suggests that patients with FMD experience a similar rate of new CeAD (1% per year) as compared to patients with spontaneous CeAD in the absence of confirmed FMD [13,29].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Plouin and colleagues prospectively evaluated 469 patients from the ARCADIA FMD registry and found that 66.3% had involvement of more than one vascular bed if aneurysm and/or dissection were defined as additional FMD sites independent of focal/multifocal findings [25]. The current data support recent recommendations to screen all FMD patients with one-time head-to-pelvis cross-sectional imaging (CTA or MRA) [5,23,25,26]. New cervical artery FMD or a change in the appearance of baseline cervical artery FMD on subsequent imaging was not observed in any patient in the current series.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our data suggest that the prevalence of renal FMD in young hypertensive women has been substantially underestimated, that limiting screening to patients ≤ 30 years old when the mean age at diagnosis in current series and registries is over 50 years old will lead to miss a substantial number of cases and finally that renal duplex has not enough sensitivity to detect all cases of renal FMD. In particular, in 2 out of 5 newly diagnosed patients with FMD reported in this study, renal duplex failed to detect FMD‐related lesions.…”
Section: Discussionmentioning
confidence: 85%
“…In the European expert Consensus, screening for renal FMD is recommended in hypertensive patients, aged under 30 years, especially in women. However, in the first report from the US FMD registry, the mean age at diagnosis of FMD was 51.9 years, in the ARCADIA study it was 53 years and in the European/International registry it is currently 45.8 years . Along the same lines, the mean age at hypertension diagnosis is 43.1 years in the US registry and 36.5 years in the European/International registry, which is substantially higher than the 30 years old cut‐off proposed in the European consensus .…”
Section: Introductionmentioning
confidence: 89%
“…The mainstay of therapy is identification of ILAA using non-invasive neuroimaging, and mediation of various risk factors such as hyperlipidemia and diabetes. Currently, the presence of ILAA is presumed by the presence of focal luminal narrowing on lumen-based imaging such as brain CTA or MRA or by identifying the presence of arterial calcifications on brain CT. 3 However, not all brain arterial stenosis are atherosclerotic, as in cases of fibromuscular dysplasia or large artery vasculitis, 4, 5 . Further, many atherosclerotic plaques have only modest degrees of luminal stenosis.…”
Section: Introductionmentioning
confidence: 99%